Manajemen Strategis Berbasis Data dan Transformasi Digital dalam Meningkatkan Mutu Pendidikan: Systematic Literature Review - Desmawati; Erlian Eka Damayanti; Evi Gusliana; Nirva Diana; Aan Komariah; Badrudin (WISE Pendidikan Indonesia, 2026)
This study aims to synthesize the literature on data-driven strategic management and digital transformation in improving educational quality. This review is important because educational institutions are increasingly required to make evidence-based decisions, integrate information systems, and transform data into impactful improvement strategies. The method employed was a Systematic Literature Review by adapting PRISMA 2020 and PRISMA-S. The literature search was conducted through Scopus, Web of Science, ERIC, DOAJ, Crossref, Google Scholar, Garuda/SINTA, and official Indonesian policy sources using keywords related to data-driven decision making, data-based planning, strategic educational management, digital transformation, Rapor Pendidikan, and educational quality. From 773 initial records, 153 duplicates were removed, 620 documents were screened, 144 full-text documents were assessed for eligibility, and 35 core documents were thematically analyzed. The findings indicate that data-driven educational quality improvement requires the integration of quality diagnosis, data interpretation, strategy formulation, digital program implementation, impact evaluation, and continuous correction. Key enabling factors include digital leadership, teachers’ data literacy, collaborative culture, data validity, technological infrastructure, and policy support. The main barriers include administrative orientation, fragmentation of information systems, gaps in analytical capacity, organizational resistance, and data ethics risks. This review proposes the SIGAP-DIGITAL model as a conceptual contribution to evidence-based educational quality governance.